Elucidating the chemical nature of laccase-modified alkyl gallates. (3rd July 2020) - Cusola, Oriol; Valls, Cristina; Vidal, Teresa; Roncero, M. Blanca
Abstract: In the first part of the present work, relevant findings concerning the laccase (Lacc) activation of alkyl gallates, and its implementation in developing hydrophobic properties on cellulose-based substrates are reported. Surface state energy by water contact angle (CA), absorption tests, and Cobb60 measurements were used to assess the hydrophobic behavior of treated substrates. SEM images of paper samples treated with functionalization solutions (FS) revealed the presence of lauryl gallate (LG, dodecyl 3, 4, 5, -trihydroxybenzoate) particles attached to fiber surfaces. Secondly, the chemical structure of the enzyme-oxidized LG and several gallates of variable chain length was elucidated by using Fourier transform infrared (FTIR) spectroscopy, and a plausible oxidation mechanism was developed. Based on them, the hydrocarbon chain of LG remains unaltered after enzyme oxidation, while the aromatic ring is significantly altered to form acidic adducts undergoing strong hydrogen bonding. Possible routes for the grafting of enzyme-modified LG to cellulose are proposed.